Preparation method and application of manganese-based Prussian blue / reduced graphene oxide composite material

By preparing manganese-based Prussian blue/reduced graphene oxide composite materials, the problems of low efficiency, poor rate and unstable cycle during the charging and discharging process of existing Prussian blue analogs are solved, and the conductivity and contact area of ​​the material are improved, which significantly improves the storage capacity of zinc ions and the use cycle of the battery.

CN119581476AActive Publication Date: 2025-03-07HEFEI UNIV OF TECH
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
CN202411803102.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-07
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

The existing Prussian blue analogs (PBAs) have disadvantages such as low efficiency, poor rate and unstable cycle during charging and discharging, which are mainly due to the rapid precipitation during the preparation process, incomplete reaction, and a large number of defects and crystallization water in the crystal structure.

Method used

Using the preparation method of manganese-based Prussian blue/reduced graphene oxide composite material, a three-dimensional frame structure was prepared by dissolving manganese sulfate monohydrate and potassium ferrocyanide monohydrate in aqueous polyvinylpyrrolidone solution, and adding potassium ferrocyanide solution at a drop speed, and then leaving it in a hydrothermal reaction with reduced graphene oxide.

Benefits of technology

It significantly improves the conductivity and contact area of ​​the material, promotes the diffusion rate of ions, effectively improves the storage location of zinc ions, improves the electrochemical performance, extends the battery life cycle, and improves reliability and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581476A_ABST
    Figure CN119581476A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a manganese-based Prussian blue / reduced graphene oxide composite material, and the method comprises the following steps: dissolving manganese sulfate monohydrate in a polyvinylpyrrolidone aqueous solution, uniformly stirring, adding a potassium ferricyanide aqueous solution while stirring, and then standing, centrifuging, washing and drying to obtain a manganese-based Prussian blue / reduced graphene oxide composite material; manganese-based Prussian blue is prepared; and adding manganese-based Prussian blue and ascorbic acid into the reduced graphene oxide dispersion liquid, stirring, transferring into a high-pressure reaction kettle, carrying out hydrothermal reaction, cooling to room temperature, centrifuging, washing, and drying to obtain the manganese-based Prussian blue / reduced graphene oxide composite material with the three-dimensional frame structure. The manganese-based Prussian blue / reduced graphene oxide composite material is used for preparing a positive electrode material of an aqueous zinc ion battery. According to the invention, the conductivity and the contact area of the material are obviously improved, the diffusion rate of ions is promoted, and the storage sites of zinc ions are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy materials and devices, and in particular to a preparation method and application of a manganese-based Prussian blue / reduced graphene oxide composite material. Background Art

[0002] With the large-scale burning of fossil fuels, non-renewable energy may be in short supply, and environmental pollution problems are becoming increasingly serious. It is urgent to develop efficient and clean renewable energy and explore newer energy storage devices. Among various energy storage systems, economical, green, safe and reliable secondary batteries have created a new way of energy storage. The development of rechargeable batteries plays a vital and indispensable role in the current energy storage industry. Lithium-ion batteries have a higher energy density and a more mature market, and are widely used in the electronic equipment industry. However, lithium-ion batteries have limited lithium resources and high costs, and their internal organic electrolytes are flammable and have low safety performance, which limits their large-scale application in life. Therefore, it is particularly important to develop alternative rechargeable batteries, and more and more researchers have begun to study other secondary batteries.

[0003] Aqueous zinc-ion batteries (AZIBs) have the advantages of abundant zinc resources, high capacity (theoretical capacity 819 mAh / g), low production cost, high safety performance, and green environmental protection, and are suitable for wide application in the field of large-scale energy storage. Common positive electrode materials include manganese-based oxides, vanadium-based oxides, Prussian blue analogs, organic compounds, etc. Among them, Prussian blue analogs (PBAs) are mixed-valence complexes with abundant redox active sites. In addition, the open three-dimensional framework structure and large ion channels in the lattice are very suitable for Zn 2+ Due to its simple preparation process, low cost, high voltage, and environmental friendliness, it has become a promising positive electrode material for AZIBs. In theory, PBAs have excellent electrochemical zinc storage performance. However, in actual charging and discharging processes, they generally have disadvantages such as low efficiency, poor rate, and unstable cycles. The reason for this is generally believed to be that during the preparation of PBAs, precipitation is too fast, the reaction is incomplete, and there are a large number of defects and crystal water in the crystal structure. Summary of the invention

[0004] The object of the present invention is to provide a preparation method and application of a manganese-based Prussian blue / reduced graphene oxide composite material, wherein the specific capacity of a battery prepared by the composite material is improved to a certain extent, the rate performance is better, and the recovery is higher.

[0005] In one aspect of the present invention, the present invention provides a method for preparing a manganese-based Prussian blue / reduced graphene oxide composite material. According to an embodiment of the present invention, the method comprises the following steps:

[0006] (1) dissolving manganese sulfate monohydrate in a polyvinyl pyrrolidone aqueous solution and stirring evenly, controlling the dripping rate, adding a potassium ferrocyanide aqueous solution while stirring, and then standing, centrifuging, washing, and drying to prepare a manganese-based Prussian blue;

[0007] (2) adding manganese-based Prussian blue and ascorbic acid to a dispersion of reduced graphene oxide, stirring and transferring the mixture to a high-pressure reactor for a hydrothermal reaction, cooling the mixture to room temperature, centrifuging, washing and drying the mixture to obtain a manganese-based Prussian blue / reduced graphene oxide composite material having a three-dimensional framework structure.

[0008] In addition, the method for preparing a manganese-based Prussian blue / reduced graphene oxide composite material according to the above embodiment of the present invention may also have the following additional technical features:

[0009] In some embodiments of the present invention, the molar ratio of polyvinyl pyrrolidone, manganese sulfate monohydrate, potassium ferrocyanide, and reduced graphene oxide is 0.037:4.81:4.81:(5-12.5).

[0010] In some embodiments of the present invention, in step (1): a peristaltic pump is used to control the dripping rate, and the dripping rate controlled by the peristaltic pump is 1-3 mL / min; the centrifugal speed is 8000-9500 rpm, and the centrifugal time is 3-6 minutes; the washing is performed by alternating anhydrous ethanol and deionized water for 3-5 times; the drying temperature is 80-120°C, and the drying time is 8-12 hours.

[0011] In some embodiments of the present invention, in step (2): the hydrothermal reaction is kept at 120-150°C for 6-8 hours; the centrifugal speed is 8000-9500 rpm, and the centrifugal time is 3-6 minutes; the washing is performed by alternating anhydrous ethanol and deionized water for 3-5 times; the drying is performed by freeze drying or vacuum drying, the freeze drying temperature is -(70-100)°C, and the freezing time is 24-48 hours; the vacuum drying temperature is 70-90°C, and the drying time is 8-12 hours.

[0012] In another aspect of the present invention, the present invention provides a manganese-based Prussian blue / reduced graphene oxide composite material prepared according to the preparation method of the manganese-based Prussian blue / reduced graphene oxide composite material.

[0013] In another aspect of the present invention, the present invention provides a positive electrode material. According to an embodiment of the present invention, the positive electrode material is prepared using the manganese-based Prussian blue / reduced graphene oxide composite material.

[0014] In another aspect of the present invention, the present invention provides a method for preparing a positive electrode material. According to an embodiment of the present invention, the method comprises the following steps:

[0015] The manganese-based Prussian blue / reduced graphene oxide composite material is evenly ground with a binder and a conductive agent, and N-methylpyrrolidone solvent is added dropwise, and the grinding and mixing are continued to be evenly applied on a stainless steel foil, vacuum dried, and cut to obtain a MnHCF-RGO electrode sheet, which is the positive electrode material.

[0016] In addition, the method for preparing a positive electrode material according to the above embodiment of the present invention may also have the following additional technical features:

[0017] In some embodiments of the present invention, the mass ratio of the manganese-based Prussian blue / reduced graphene oxide composite material, the conductive agent, and the binder is (7-8):(2-1):1, the binder used is polyvinylidene fluoride, and the conductive agent is Ketjen black.

[0018] In another aspect of the present invention, the present invention provides an aqueous zinc ion battery. According to an embodiment of the present invention, the positive electrode material is used as the positive electrode.

[0019] In addition, an aqueous zinc ion battery according to the above embodiment of the present invention may also have the following additional technical features:

[0020] In some embodiments of the present invention, the negative electrode material is a zinc electrode sheet, the electrolyte is a mixture of zinc sulfate and manganese sulfate, and the battery separator is glass fiber.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1) The addition of graphene oxide in the present invention can significantly enhance the conductivity of manganese-based Prussian blue, greatly increase the charge transfer rate of the material, and accelerate the electrochemical reaction rate. At the same time, graphene oxide can also serve as a buffer matrix to alleviate the structural collapse phenomenon that may occur in manganese-based Prussian blue during the charging and discharging process. This composite strategy not only effectively improves the electrochemical performance, but also can greatly extend the service life of the battery and improve its reliability and safety. Secondly, graphene oxide can also serve as a structural stabilizer to stabilize the structure of the material, thereby effectively improving the electrochemical performance of the material.

[0023] 2) The present invention utilizes the advantages of reduced graphene oxide, such as good conductivity, low resistance, and fast electron transmission speed, so that the manganese-based Prussian blue complex with a three-dimensional framework structure forms a large network structure as a whole, which significantly improves the conductivity of the material and the contact area of ​​the material, promotes the diffusion rate of ions, and effectively increases the storage sites of zinc ions.

[0024] 3) The present invention adopts freeze drying and vacuum drying technology. It can be seen from the SEM image that manganese-based Prussian blue cubes are distributed in the layered reduced graphene oxide, which effectively prevents the agglomeration of particles. The overall structure is relatively uniform and has a higher specific surface area. The material has good stability and high specific capacity during the charge and discharge process. After composite graphene, the initial specific capacity is 104mAh / g at a current density of 0.1A / g. After the rate test, when the current density of 0.1A / g is used again, the discharge specific capacity recovery rate reaches 110.9%, the battery specific capacity is improved to a certain extent, the rate performance is better, and the recovery is higher.

[0025] 4) The preparation process of the present invention is simple, the reaction conditions are mild, the environment is friendly, and the cost is low. It has great application value and is also applicable to other Prussian blue analogue positive electrode materials.

[0026] 5) The present invention uses a peristaltic pump to accurately control the flow rate, adopts a slow crystallization method to prepare a manganese-based Prussian blue with a complete structure, and then adopts a high-temperature hydrothermal method to compositely reduce graphene oxide, thereby solving the problem of incomplete reaction caused by too fast precipitation during the preparation of PBAs, and finally obtains a manganese-based Prussian blue / reduced graphene oxide composite material with better electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The XRD spectra of the manganese-based Prussian blue (a) prepared in step 1 of Example 1 of the present invention and the manganese-based Prussian blue / reduced graphene oxide with a three-dimensional framework structure prepared in Examples 1 and 2 (b);

[0028] Figure 2 1 is a SEM image of the manganese-based Prussian blue (a) prepared in Example 1 of the present invention and the manganese-based Prussian blue / reduced graphene oxide having a three-dimensional framework structure (b);

[0029] Figure 3 The AC impedance spectra of the manganese-based Prussian blue prepared in Example 1 of the present invention and the manganese-based Prussian blue / reduced graphene oxide with a three-dimensional framework structure prepared in Examples 1 and 2;

[0030] Figure 4 1 is a cycle diagram of the manganese-based Prussian blue (a) prepared in Example 1 of the present invention and the manganese-based Prussian blue / reduced graphene oxide having a three-dimensional framework structure prepared in Example 1 (b) and Example 2 (c);

[0031] Figure 5 It is a rate diagram of the manganese-based Prussian blue prepared in Example 1 of the present invention and the manganese-based Prussian blue / reduced graphene oxide with a three-dimensional framework structure prepared in Examples 1 and 2. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Example 1

[0034] A method for preparing a manganese-based Prussian blue / reduced graphene oxide composite material comprises the following steps:

[0035] (1) Weigh 2.221 g of polyvinyl pyrrolidone and dissolve it in 120 mL of deionized water. Then weigh 0.813 g of manganese sulfate monohydrate and dissolve it in the polyvinyl pyrrolidone aqueous solution. Stir well to prepare solution A. Weigh 1.584 g of potassium ferrocyanide and dissolve it in 60 mL of deionized water. Stir well to prepare orange-red solution B. Use a peristaltic pump to slowly drop solution B into solution A at a rate of 1 mL / min while stirring. The solution after the reaction is brown. After the reaction is completed, let it stand for 12 hours, then centrifuge it at 8000 rpm for 5 minutes, and wash it alternately with anhydrous ethanol and deionized water for 3 times. Place the obtained sample in a forced air drying oven and dry it at 80°C for 8 hours to obtain a brown powder, which is the prepared manganese-based Prussian blue (MnHCF).

[0036] (2) Weigh 60 mg of reduced graphene oxide and disperse it in 30 mL of deionized water, and ultrasonically treat it for 3 h to obtain a uniformly dispersed 2 mg / mL graphene dispersion. Weigh 100 mg of the manganese-based Prussian blue prepared in step (1) and 50 mg of ascorbic acid and add them to 30 mL of the reduced graphene oxide dispersion, ultrasonically disperse it for 1 h, and then magnetically stir it for 12 h. Then, transfer the suspension to a 100 mL high-pressure reactor, keep it in an oven at 120° C. for 6 h, cool it to room temperature, centrifuge it at 8000 rpm for 5 minutes, wash it alternately with anhydrous ethanol and deionized water for 3 times, and finally place it in a freeze dryer for freeze drying at a freezing temperature of -70° C. for 24 hours to obtain a manganese-based Prussian blue / reduced graphene oxide (MnHCF-RGO) composite material with a three-dimensional framework structure.

[0037] like Figure 1As shown, the manganese-based Prussian blue sample prepared in step (1) corresponds to PDF card #00-052-1907, indicating that the composition of the sample prepared in step (1) of this application is Mn3[Fe(CN)6]2. All diffraction peaks of the sample prepared in step (2) correspond to the two standard cards of Mn3[Fe(CN)6]2 (PDF#00-052-1907) and C (PDF#41-1487), and the sharp diffraction peak at 26.3° corresponds to the (002) crystal plane of C, indicating that the manganese-based Prussian blue / reduced graphene oxide (MnHCF-RGO) composite material was successfully prepared by freeze drying.

[0038] like Figure 2 As shown, the manganese-based Prussian blue sample prepared in step (1) is a uniform cubic block, and the sample prepared in step (2) is a layered graphene with MnHCF cubic blocks distributed in it, indicating that the introduction of graphene does not change the original morphological characteristics of MnHCF, and the overall structure is relatively uniform. The hydrothermal method allows graphene and manganese-based Prussian blue to be well composited.

[0039] Example 2

[0040] A method for preparing a manganese-based Prussian blue / reduced graphene oxide composite material comprises the following steps:

[0041] (1) Weigh 2.221 g of polyvinyl pyrrolidone and dissolve it in 120 mL of deionized water. Then weigh 0.813 g of manganese sulfate monohydrate and dissolve it in the polyvinyl pyrrolidone aqueous solution. Stir well to prepare solution A. Weigh 1.584 g of potassium ferrocyanide and dissolve it in 60 mL of deionized water. Stir well to prepare orange-red solution B. Use a peristaltic pump to slowly drop solution B into solution A at a rate of 1 mL / min while stirring. The solution after the reaction is brown. After the reaction is completed, let it stand for 12 hours, then centrifuge it at 8000 rpm for 5 minutes, and wash it alternately with anhydrous ethanol and deionized water for 3 times. Place the obtained sample in a blast drying oven and dry it at 80°C for 8 hours to obtain a brown powder, which is the prepared manganese-based Prussian blue (MnHCF).

[0042] (2) Weigh 60 mg of reduced graphene oxide and disperse it in 30 mL of deionized water. Ultrasonicate for 3 h to obtain a uniformly dispersed 2 mg mL -1100 mg of the manganese-based Prussian blue prepared in step (1) and 50 mg of ascorbic acid were weighed and added to 30 mL of the reduced graphene oxide dispersion, and ultrasonically dispersed for 1 h, and then magnetically stirred for 12 h. The suspension was then transferred to a 100 mL high-pressure reactor, kept in an oven at 120 ° C for 6 h, cooled to room temperature, and centrifuged at 8000 rpm for 5 min. The mixture was washed alternately with anhydrous ethanol and deionized water for 3 times, and finally placed in a vacuum drying oven for vacuum drying at a temperature of 80 ° C and a drying time of 12 hours. The manganese-based Prussian blue / reduced graphene oxide (MnHCF-RGO) composite material with a three-dimensional framework structure was prepared.

[0043] Example 3

[0044] A method for preparing a manganese-based Prussian blue / reduced graphene oxide composite material comprises the following steps:

[0045] (1) Weigh 2.221 g of polyvinyl pyrrolidone and dissolve it in 120 mL of deionized water. Then weigh 0.813 g of manganese sulfate monohydrate and dissolve it in the polyvinyl pyrrolidone aqueous solution. Stir well to prepare solution A. Weigh 1.584 g of potassium ferrocyanide and dissolve it in 60 mL of deionized water. Stir well to prepare orange-red solution B. Use a peristaltic pump to slowly drop solution B into solution A at a rate of 1 mL / min while stirring. The solution after the reaction is brown. After the reaction is completed, let it stand for 12 hours, then centrifuge it at 8000 rpm for 5 minutes, and wash it alternately with anhydrous ethanol and deionized water for 3 times. Place the obtained sample in a blast drying oven and dry it at 80°C for 8 hours to obtain a brown powder, which is the prepared manganese-based Prussian blue (MnHCF).

[0046] (2) Weigh 90 mg of reduced graphene oxide and disperse it in 30 mL of deionized water. Ultrasonicate for 3 h to obtain a uniformly dispersed 3 mg mL -1 100 mg of the manganese-based Prussian blue prepared in step (1) and 50 mg of ascorbic acid were weighed and added to 30 mL of the reduced graphene oxide dispersion, and ultrasonically dispersed for 1 hour, and then magnetically stirred for 12 hours. After that, the suspension was transferred to a 100 mL high-pressure reactor, kept warm in an oven at 120° C. for 6 hours, cooled to room temperature, and centrifuged at 8000 rpm for 5 minutes. The mixture was washed alternately with anhydrous ethanol and deionized water for 3 times, and finally placed in a freeze dryer for freeze drying at a freezing temperature of -70° C. for 24 hours to obtain a manganese-based Prussian blue / reduced graphene oxide (MnHCF-RGO) composite material with a three-dimensional framework structure.

[0047] Example 4

[0048] A method for preparing a manganese-based Prussian blue / reduced graphene oxide composite material comprises the following steps:

[0049] (1) Weigh 2.221 g of polyvinyl pyrrolidone and dissolve it in 120 mL of deionized water. Then weigh 0.813 g of manganese sulfate monohydrate and dissolve it in the polyvinyl pyrrolidone aqueous solution. Stir well to prepare solution A. Weigh 1.584 g of potassium ferrocyanide and dissolve it in 60 mL of deionized water. Stir well to prepare orange-red solution B. Use a peristaltic pump to slowly drop solution B into solution A at a rate of 1 mL / min while stirring. The solution after the reaction is brown. After the reaction is completed, let it stand for 12 hours, then centrifuge it at 8000 rpm for 5 minutes, and wash it alternately with anhydrous ethanol and deionized water for 3 times. Place the obtained sample in a blast drying oven and dry it at 80°C for 8 hours to obtain a brown powder, which is the prepared manganese-based Prussian blue (MnHCF).

[0050] (2) Weigh 90 mg of reduced graphene oxide and disperse it in 30 mL of deionized water. Ultrasonicate for 3 h to obtain a uniformly dispersed 3 mg mL -1 100 mg of the manganese-based Prussian blue prepared in step (1) and 50 mg of ascorbic acid were weighed and added to 30 mL of the reduced graphene oxide dispersion, and ultrasonically dispersed for 1 h, and then magnetically stirred for 12 h. The suspension was then transferred to a 100 mL high-pressure reactor, kept in an oven at 120 ° C for 6 h, cooled to room temperature, and centrifuged at 8000 rpm for 5 min. The mixture was washed alternately with anhydrous ethanol and deionized water for 3 times, and finally placed in a vacuum drying oven for vacuum drying at a temperature of 80 ° C and a drying time of 12 hours. The manganese-based Prussian blue / reduced graphene oxide (MnHCF-RGO) composite material with a three-dimensional framework structure was prepared.

[0051] Example 5

[0052] A method for preparing a manganese-based Prussian blue / reduced graphene oxide composite material comprises the following steps:

[0053] (1) Weigh 2.221 g of polyvinyl pyrrolidone and dissolve it in 120 mL of deionized water. Then weigh 0.813 g of manganese sulfate monohydrate and dissolve it in the polyvinyl pyrrolidone aqueous solution. Stir well to prepare solution A. Weigh 1.584 g of potassium ferrocyanide and dissolve it in 60 mL of deionized water. Stir well to prepare orange-red solution B. Use a peristaltic pump to slowly drop solution B into solution A at a rate of 1 mL / min while stirring. The solution after the reaction is brown. After the reaction is completed, let it stand for 12 hours, then centrifuge it at 8000 rpm for 5 minutes, and wash it alternately with anhydrous ethanol and deionized water for 3 times. Place the obtained sample in a blast drying oven and dry it at 80°C for 8 hours to obtain a brown powder, which is the prepared manganese-based Prussian blue (MnHCF).

[0054] (2) Weigh 120 mg of reduced graphene oxide and disperse it in 30 mL of deionized water. Ultrasonicate for 3 h to obtain a uniformly dispersed 4 mg mL -1 100 mg of the manganese-based Prussian blue prepared in step (1) and 50 mg of ascorbic acid were weighed and added to 30 mL of the reduced graphene oxide dispersion, and ultrasonically dispersed for 1 hour, and then magnetically stirred for 12 hours. After that, the suspension was transferred to a 100 mL high-pressure reactor, kept warm in an oven at 120° C. for 6 hours, cooled to room temperature, and centrifuged at 8000 rpm for 5 minutes. The mixture was washed alternately with anhydrous ethanol and deionized water for 3 times, and finally placed in a freeze dryer for freeze drying at a freezing temperature of -70° C. for 24 hours to obtain a manganese-based Prussian blue / reduced graphene oxide (MnHCF-RGO) composite material with a three-dimensional framework structure.

[0055] Example 6

[0056] A method for preparing a manganese-based Prussian blue / reduced graphene oxide composite material comprises the following steps:

[0057] (1) Weigh 2.221 g of polyvinyl pyrrolidone and dissolve it in 120 mL of deionized water. Then weigh 0.813 g of manganese sulfate monohydrate and dissolve it in the polyvinyl pyrrolidone aqueous solution. Stir well to prepare solution A. Weigh 1.584 g of potassium ferrocyanide and dissolve it in 60 mL of deionized water. Stir well to prepare orange-red solution B. Use a peristaltic pump to slowly drop solution B into solution A at a rate of 1 mL / min while stirring. The solution after the reaction is brown. After the reaction is completed, let it stand for 12 hours, then centrifuge it at 8000 rpm for 5 minutes, and wash it alternately with anhydrous ethanol and deionized water for 3 times. Place the obtained sample in a blast drying oven and dry it at 80°C for 8 hours to obtain a brown powder, which is the prepared manganese-based Prussian blue (MnHCF).

[0058] (2) Weigh 120 mg of reduced graphene oxide and disperse it in 30 mL of deionized water. Ultrasonicate for 3 h to obtain a uniformly dispersed 4 mg mL -1 100 mg of the manganese-based Prussian blue prepared in step (1) and 50 mg of ascorbic acid were weighed and added to 30 mL of the reduced graphene oxide dispersion, and ultrasonically dispersed for 1 h, and then magnetically stirred for 12 h. The suspension was then transferred to a 100 mL high-pressure reactor, kept in an oven at 120 ° C for 6 h, cooled to room temperature, and centrifuged at 8000 rpm for 5 min. The mixture was washed alternately with anhydrous ethanol and deionized water for 3 times, and finally placed in a vacuum drying oven for vacuum drying at a temperature of 80 ° C and a drying time of 12 hours. The manganese-based Prussian blue / reduced graphene oxide (MnHCF-RGO) composite material with a three-dimensional framework structure was prepared.

[0059] Example 7

[0060] A method for preparing a manganese-based Prussian blue / reduced graphene oxide composite material comprises the following steps:

[0061] (1) Weigh 2.221 g of polyvinyl pyrrolidone and dissolve it in 120 mL of deionized water. Then weigh 0.813 g of manganese sulfate monohydrate and dissolve it in the polyvinyl pyrrolidone aqueous solution. Stir well to prepare solution A. Weigh 1.584 g of potassium ferrocyanide and dissolve it in 60 mL of deionized water. Stir well to prepare orange-red solution B. Use a peristaltic pump to slowly drop solution B into solution A at a rate of 1 mL / min while stirring. The solution after the reaction is brown. After the reaction is completed, let it stand for 12 hours, then centrifuge it at 8000 rpm for 5 minutes, and wash it alternately with anhydrous ethanol and deionized water for 3 times. Place the obtained sample in a blast drying oven and dry it at 80°C for 8 hours to obtain a brown powder, which is the prepared manganese-based Prussian blue (MnHCF).

[0062] (2) Weigh 150 mg of reduced graphene oxide and disperse it in 30 mL of deionized water. Ultrasonicate for 3 h to obtain a uniformly dispersed 5 mg mL -1 100 mg of the manganese-based Prussian blue prepared in step (1) and 50 mg of ascorbic acid were weighed and added to 30 mL of the reduced graphene oxide dispersion, and ultrasonically dispersed for 1 hour, and then magnetically stirred for 12 hours. After that, the suspension was transferred to a 100 mL high-pressure reactor, kept warm in an oven at 120° C. for 6 hours, cooled to room temperature, and centrifuged at 8000 rpm for 5 minutes. The mixture was washed alternately with anhydrous ethanol and deionized water for 3 times, and finally placed in a freeze dryer for freeze drying at a freezing temperature of -70° C. for 24 hours to obtain a manganese-based Prussian blue / reduced graphene oxide (MnHCF-RGO) composite material with a three-dimensional framework structure.

[0063] Example 8

[0064] A method for preparing a manganese-based Prussian blue / reduced graphene oxide composite material comprises the following steps:

[0065] (1) Weigh 2.221 g of polyvinyl pyrrolidone and dissolve it in 120 mL of deionized water. Then weigh 0.813 g of manganese sulfate monohydrate and dissolve it in the polyvinyl pyrrolidone aqueous solution. Stir well to prepare solution A. Weigh 1.584 g of potassium ferrocyanide and dissolve it in 60 mL of deionized water. Stir well to prepare orange-red solution B. Use a peristaltic pump to slowly drop solution B into solution A at a rate of 1 mL / min while stirring. The solution after the reaction is brown. After the reaction is completed, let it stand for 12 hours, then centrifuge it at 8000 rpm for 5 minutes, and wash it alternately with anhydrous ethanol and deionized water for 3 times. Place the obtained sample in a blast drying oven and dry it at 80°C for 8 hours to obtain a brown powder, which is the prepared manganese-based Prussian blue (MnHCF).

[0066] (2) Weigh 150 mg of reduced graphene oxide and disperse it in 30 mL of deionized water. Ultrasonicate for 3 h to obtain a uniformly dispersed 5 mg mL -1 100 mg of the manganese-based Prussian blue prepared in step (1) and 50 mg of ascorbic acid were weighed and added to 30 mL of the reduced graphene oxide dispersion, and ultrasonically dispersed for 1 h, and then magnetically stirred for 12 h. The suspension was then transferred to a 100 mL high-pressure reactor, kept in an oven at 120 ° C for 6 h, cooled to room temperature, and centrifuged at 8000 rpm for 5 min. The mixture was washed alternately with anhydrous ethanol and deionized water for 3 times, and finally placed in a vacuum drying oven for vacuum drying at a temperature of 80 ° C and a drying time of 12 hours. The manganese-based Prussian blue / reduced graphene oxide (MnHCF-RGO) composite material with a three-dimensional framework structure was prepared.

[0067] Application Example 1

[0068] A method for preparing a positive electrode material comprises the following steps:

[0069] The MnHCF prepared in Example 1 and the MnHCF-RGO prepared in Examples 1 and 2 were respectively mixed with Ketjen black and PVDF in a mass ratio of 7:2:1, a small amount of NMP solvent was added dropwise, and the mixture was ground and mixed evenly. The slurry was coated on a stainless steel bowl, vacuum dried at 80° C. for 12 h, and cut into electrode sheets with a diameter of 12 mm using a slicer to obtain electrode sheets, i.e., positive electrode materials.

[0070] Application Example 2

[0071] The preparation method of an aqueous zinc ion battery comprises the following steps:

[0072] A zinc pot with a thickness of 0.02 mm and a purity of 99.9% was polished with sandpaper to remove the oxide film, and then cut into zinc electrode sheets with a diameter of 12 mm as the negative electrode. The electrode sheet prepared in Application Example 1 was used as the positive electrode material, a mixture of 3M zinc sulfate and 0.5M manganese sulfate was used as the electrolyte, and a glass fiber with a diameter of 16 mm was used as the battery separator to assemble a button-type CR2025 aqueous zinc ion battery.

[0073] like Figure 3 As shown, in the high-frequency region, the semicircle radius of the MnHCF-RGO prepared by freeze-drying method in Example 1 and by vacuum drying method in Example 2 is the smallest, indicating that after freeze-drying method composite graphene, the charge transfer resistance Rct at the electrode / electrolyte interface is the smallest. At the same time, in the low-frequency region, the slope of the oblique line of the MnHCF-RGO sample prepared by freeze-drying method in Example 1 is the largest, indicating that after freeze-drying method composite graphene, ion diffusion is faster, which increases the charge transfer rate of the material and accelerates the electrochemical reaction rate.

[0074] like Figure 4 As shown, the initial specific capacity of MnHFC-RGO prepared by freeze-drying method in Example 1 is 104 mAh / g at a current density of 0.1 A / g. Compared with the manganese-based Prussian blue sample prepared in step (1) of Example 1, the composite graphene significantly improves the specific capacity of MnHFC. After 50 cycles, the battery specific capacity drops to 75 mAh / g. After 200 cycles, the battery specific capacity becomes 68 mAh / g. After 50 cycles, the capacity retention rate reaches 91%.

[0075] like Figure 5 As shown, when the MnHCF-RGO sample prepared by freeze-drying was re-tested with a current density of 0.1A / g after rate testing, the discharge specific capacity recovery rate reached 110.9%. The battery specific capacity was improved to a certain extent, the rate performance was better, and the recovery was higher.

[0076] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the present invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing a manganese-based Prussian blue / reduced graphene oxide composite material, characterized in that: The following steps are involved: (1) dissolving manganese sulfate monohydrate in a polyvinyl pyrrolidone aqueous solution and stirring evenly, controlling the dripping rate, adding a potassium ferrocyanide aqueous solution while stirring, and then standing, centrifuging, washing, and drying to prepare a manganese-based Prussian blue; (2) adding manganese-based Prussian blue and ascorbic acid to a dispersion of reduced graphene oxide, stirring and transferring the mixture to a high-pressure reactor for a hydrothermal reaction, cooling the mixture to room temperature, centrifuging, washing and drying the mixture to obtain a manganese-based Prussian blue / reduced graphene oxide composite material having a three-dimensional framework structure.

2. The method for preparing a manganese-based Prussian blue / reduced graphene oxide composite material according to claim 1, characterized in that: The molar ratio of the polyvinyl pyrrolidone, manganese sulfate monohydrate, potassium ferrocyanide and reduced graphene oxide is 0.037:4.81:4.81:(5-12.5).

3. The method for preparing a manganese-based Prussian blue / reduced graphene oxide composite material according to claim 1, characterized in that: In step (1): The dripping rate is 1-3 mL / min; The centrifugal speed is 8000-9500 rpm, and the centrifugal time is 3-6 minutes; The washing is performed by alternating anhydrous ethanol and deionized water for 3-5 times; The drying temperature is 80-120° C., and the drying time is 8-12 hours.

4. The method for preparing a manganese-based Prussian blue / reduced graphene oxide composite material according to claim 1, characterized in that: In step (2): The hydrothermal reaction is carried out at 120-150° C. for 6-8 hours; The centrifugal speed is 8000-9500 rpm, and the centrifugal time is 3-6 minutes; The washing is performed by alternating anhydrous ethanol and deionized water for 3-5 times; The drying is carried out by freeze drying or vacuum drying. The freeze drying temperature is -(70-100)°C for 24-48 hours. The vacuum drying temperature is 70-90°C for 8-12 hours.

5. A manganese-based Prussian blue / reduced graphene oxide composite material prepared according to the method for preparing a manganese-based Prussian blue / reduced graphene oxide composite material according to any one of claims 1 to 4.

6. A positive electrode material, characterized in that: Prepared using the manganese-based Prussian blue / reduced graphene oxide composite material described in claim 5.

7. A method for preparing the positive electrode material according to claim 6, characterized in that: The following steps are involved: The manganese-based Prussian blue / reduced graphene oxide composite material is evenly ground with a binder and a conductive agent, and N-methylpyrrolidone solvent is added dropwise, and the grinding and mixing are continued to be evenly applied on a stainless steel foil, vacuum dried, and cut to obtain a MnHCF-RGO electrode sheet, which is the positive electrode material.

8. The method for preparing a positive electrode material according to claim 7, characterized in that: The mass ratio of the manganese-based Prussian blue / reduced graphene oxide composite material, the conductive agent, and the binder is (7-8):(2-1):1, the binder used is polyvinylidene fluoride, and the conductive agent is Ketjen black.

9. An aqueous zinc ion battery, characterized in that: The positive electrode material according to claim 6 is used as the positive electrode.

10. An aqueous zinc ion battery according to claim 9, characterized in that: The negative electrode material is a zinc electrode sheet, the electrolyte is a mixture of zinc sulfate and manganese sulfate, and the battery separator is glass fiber.

Citation Information

Patent Citations

  • Method for preparing prussian blue material through composite reduction of graphene oxide, and application

    CN108217630A

  • Graphene rapidly-coated Prussian blue sodium ion battery positive electrode material and preparation method thereof

    CN108565422A

  • High-performance Prussian blue @ graphite lithium battery composite cathode material and preparation method thereof

    CN109216674A

  • Preparation method of three-dimensional graphene network structure supported Prussian blue analog

    CN109346686A

  • Preparation method of hollow cobalt-based Prussian blue electrode material

    CN114873610A